Carbonic Anhydrase Inhibitors Targeting Metabolism and Tumor Microenvironment - Angeli, Andrea; Carta, Fabrizio; Nocentini, Alessio; Winum, Jean-Yves; Zalubovskis, Raivis; AKDEMİR, ATİLLA; AKDEMİR, ATİLLA; Onnis, Valentina; Eldehna, Wagdy M.; Capasso, Clemente; De Simone, Giuseppina; Monti, Simona Maria; et al. (My University, 2020)
The tumor microenvironment is crucial for the growth of cancer cells, triggering particular biochemical and physiological changes, which frequently influence the outcome of anticancer therapies. The biochemical rationale behind many of these phenomena resides in the activation of transcription factors such as hypoxia-inducible factor 1 and 2 (HIF-1/2). In turn, the HIF pathway activates a number of genes including those involved in glucose metabolism, angiogenesis, and pH regulation. Several carbonic anhydrase (CA, EC 4.2.1.1) isoforms, such as CA IX and XII, actively participate in these processes and were validated as antitumor/antimetastatic drug targets. Here, we review the field of CA inhibitors (CAIs), which selectively inhibit the cancer-associated CA isoforms. Particular focus was on the identification of lead compounds and various inhibitor classes, and the measurement of CA inhibitory on-/off-target effects. In addition, the preclinical data that resulted in the identification of SLC-0111, a sulfonamide in Phase Ib/II clinical trials for the treatment of hypoxic, advanced solid tumors, are detailed.